Effect of Silver Nano Particle Microalgae Chlorella pyrenoidosa and Dunaliella salina on Growth and Survival of Penaeus monodon Larvae - Hermin Pancasakti Kusumaningrum; Muhammad Zainuri; Indras Marhaendrajaya; Agus Subagio; Widianingsih Widianingsih; Hadi Endrawati; Annisa Fadillah; Muhammad Iskandar Zulkarnain; Yuvita Muliastuti; Imam Misbach (Universitas Diponegoro, 2021)
Penaeus monodon is one of the most important farmed crustaceans. Its also known as Asia Tiger Shrimp because its carapace and abdomen are transversely banded with red and white. The use of synthetic antibiotic in aquaculture had caused problems related to health and environmental safety. Chlorella pyrenoidosa and Dunaliella salina are photosynthetic microalgae. Silver nano particle in microalgae C. pyrenoidosa and D. salina had synthesized and showed their growth stability. They offer a potency to be exploited to supported growth and survival of shrimp larvae. The objective of the study was the application of silver nano particle in microalgae C. pyrenoidosa and D. salina on P. monodon larvae. The research methodology was carried out by making microalgae C. pyrenoidosa and D. salina containing silver nano particle and used as feed of shrimp larvae. Observations were made on the growth and survival of shrimp larvae compared to both microalgae and common feed. The results showed that the P. monodon larvae have the higher growth and survival rate with microalgae C. pyrenoidosa at the beginning of their growth compared to D. salina. However, microalgae without nanosilver and common feed showed a better result for growth and activity of shrimp larvae.